Monkey B-lymphotropic papovavirus mutant capable of replicating in T-lymphoblastoid cells. - Kanda, T (1985)
Monkey B-lymphotropic papovavirus (LPV) DNA present as free copies in LPV-transformed hamster embryo cells was molecularly cloned in Escherichia coli. Twenty-two of 24 cloned DNAs were 4.9 kilobases long and shorter than the wild-type LPV DNA (5.1 kilobases). The shorter DNA was nondefective and generated infectious virus (designated LPV-76) upon transfection of human B-lymphoblastoid BJA-B cells. LPV-76 DNA had a small deletion in the early region and a deletion and an insertion in the control region for transcription. LPV-76 VP-1 was apparently larger than that of the wild-type LPV. LPV-76 could grow in human T-lymphoblastoid MOLT-4 cells, whereas the wild-type LPV replicated only in B-lymphoblastoid cells. Characterization of constructed recombinant viruses between wild-type LPV and LPV-76 showed that the mutation responsible for the extended host range of LPV-76 was within the PstI B fragment, which includes the VP-1 coding region. These data strongly suggest that the mutation of VP-1 altered the host range of LPV.